Localization and Corruption : Panacea or Pandora’s Box? - Gurgur, Tugrul (World Bank, Washington, DC, 2012)
An extensive literature on the relationship between decentralization (or localization) and corruption has developed in recent years. While some authors argue that there is a positive relationship between decentralization and corruption, others claim that decentralization in fact leads to a reduction in the level of corruption. This important policy question has not yet been laid to rest, since previous empirical work simply uses eclectic regressions and lacks a conceptual framework to discover the root causes of corruption. This paper attempts to fill this void by presenting a framework in identifying the drivers of corruption both conceptually and empirically in order to isolate the role of centralized decision-making on corruption. The following results emerge: 1) For a sample of 30 countries (developing and industrial), corruption is caused by: a lack of service-orientation in the public sector, weak democratic institutions, economic isolation (closed economy), colonial past, internal bureaucratic controls and centralized decision making. 2) Decentralization is found to have a negative impact on corruption, with the effect being stronger in unitary than in federal countries.